2013
DOI: 10.1021/jp401847s
|View full text |Cite
|
Sign up to set email alerts
|

A Drude Polarizable Model for Liquid Hydrogen Sulfide

Abstract: A polarizable force field for liquid hydrogen sulfide (H2S) has been developed based on the Drude oscillator model. This force field has been designed to be analogous to the SWM4-NDP water model; the model is rigid with point charges assigned to the H and S atoms and a lone pair on the bisector of ∠HSH in the molecular plane. Positions of the lone pair and the charges have been defined such that the model has a static dipole moment of 0.98 D, equal to the experimental value. Polarizability is incorporated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 44 publications
9
49
0
Order By: Relevance
“…This is consistent with previous studies that concluded that thiol sulfurs are poor hydrogen bond acceptors due to their large radius and modest electronegativity. 19,39 These rdfs are consistent with the thiols being hydrophobic solutes, with very limited hydrogen bonding interactions with the aqueous solvent.…”
Section: Methylthiolsupporting
confidence: 59%
“…This is consistent with previous studies that concluded that thiol sulfurs are poor hydrogen bond acceptors due to their large radius and modest electronegativity. 19,39 These rdfs are consistent with the thiols being hydrophobic solutes, with very limited hydrogen bonding interactions with the aqueous solvent.…”
Section: Methylthiolsupporting
confidence: 59%
“…Beyond this conventional nonpolarizable model, the Drude polarizable force field is also supported by CHARMM . This model has been parameterized for water, ions, sulfur‐containing compounds, aromatics, amides, alkanes, alcohols, proteins, and nucleic acids …”
Section: Introductionmentioning
confidence: 99%
“…The approach was proposed by Paul Drude in 1900 26 as a simple way to describe the dispersive properties of materials and introduced into CHARMM (Chemistry at HARvard Molecular Mechanics) back in 2003. 22,27 Ever since, force field parameters based on Drude oscillator models have been developed for water, 22,28 alkanes, 29 alcohols, 30 ethers, 31 amides, 32 aromatics, 33 nitrogen-containing heteroaromatics, 34 sulfur-containing compounds, 35,36 and ions. 37,38 Those for biomolecules, such as proteins, nucleic acids, lipids, and carbohydrates, 39 are under active development.…”
Section: Introductionmentioning
confidence: 99%